The Roles of MTRR and MTHFR Gene Polymorphisms in Colorectal Cancer Survival - Yu Wang; Meizhi Du; Jillian Vallis; Matin Shariati; Patrick S. Parfrey; John R. Mclaughlin; Peizhong Peter Wang; Yun Zhu (Nutrients, 2022)
Background: Paradoxically epidemiological data illustrate a negative relationship between dietary folate intake and colorectal cancer (CRC) risk. The occurrence and progression of CRC may be influenced by variants in some key enzyme coding genes in the folate metabolic pathway. We investigated the correlation between genetic variants in methionine synthase reductase (MTRR) and methylenetetrahydrofolate reductase (MTHFR) and CRC survival. Methods: This study used data collected from the Newfoundland Familial Colorectal Cancer Study. A total of 532 patients diagnosed with CRC for the first time from 1999 to 2003 were enrolled, and their mortality were tracked until April 2010. DNA samples were genotyped by Illumina’s integrated quantum 1 million chip. Cox models were established to assess 33 tag single-nucleotide polymorphisms in MTRR and MTHFR in relation to overall survival (OS), disease-free survival (DFS) and CRC-specific survival. Results: The MTRR and MTHFR genes were associated with DFS and CRC-specific survival in CRC patients at the gene level. After multiple comparison adjustment, MTRR rs1801394 A (vs. G) allele was associated with increased DFS (p = 0.024), while MTHRT rs3737966 (G vs. A), rs4846049 (T vs. G), rs1476413 (A vs. G), rs1801131 (C vs. A), rs12121543 (A vs. C), rs1801133 (C vs. T), rs4846052 (T vs. C), rs2066471 (A vs. G) and rs7533315 (T vs. C) were related to worse CRC-specific survival. Additionally, significant interactions were seen among pre-diagnostic alcohol consumption with MTRR rs1801394, rs3776467, rs326124, rs162040, and rs3776455, with superior OS associated with those protective variant alleles limited to patients with alcohol consumption under the median. The MTHFR rs3737966 (G vs. A) allele seemed to be detrimental to CRC survival only among subjects with fruit intake below the median. Conclusions: Polymorphic variants in MTRR and MTHFR genes that code for key enzymes for folate metabolism may be associated with survival in patients with CRC. The gene-CRC outcome association ...